Philosophical foundations of the law of torts - Oberdiek, John (Oxford : Oxford University Press, 2014)
This title offers a rich insight into the law of torts and will be of broad interest to those working in legal and moral philosophy. It has contributions from all over the world and represents the state-of-the art in tort theory.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Torts -- Philosophy